Pemanfaatan LOSIDA (Lodong Sisa Dapur) sebagai Solusi dalam Mengelola Sampah Organik Menjadi Kompos di Desa Tobimeita - Nurfadilah H, Siti; Effendy, Devi Savitri; Tosepu, Ramadhan; Nurmaladewi, Nurmaladewi; Handayani, Listy; Salsabila, Syefira; Bawia, Muhammad Anugrah; Akhmadi, Khafizah Valerina; Ishak, Alya Rahmawati (Pakis Journal Institute, 2025)
Household organic waste, especially food and fruit scraps, often becomes the main source of garbage piles that cause odors, environmental pollution, and methane gas emissions if not managed properly. This problem is still common in Tobimeita Village, Motui District, North Konawe Regency. This study aims to empower the community in managing household organic waste through the simple technology of LOSIDA (Lodong Sisa Dapur). The method used is descriptive qualitative through observation, interviews, and direct practice of making and installing losida with the community. The results of the study indicate that the application of losida is effective in reducing the volume of organic waste, producing compost and liquid fertilizer, and increasing public awareness of environmental cleanliness. In addition, losida has proven to be practical to implement, environmentally friendly, and able to provide economic and ecological benefits. Therefore, the application of losida can be an alternative solution in managing household organic waste that is simple but has a significant impact on the community.